KETERAMPILAN WIRAUSAHA SISWA MELALUI PROGRAM PASAR JUMAT DALAM KURIKULUM SEKOLAH ALAM TAHFIDZ QURAN KABUPATEN MAJALENGKA - Firas Alamanda Alamanda (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This research is motivated by the urgency of entrepreneurial skills as one of the soft skills of students in social life. Entrepreneurship is also one of the areas that the government pays attention to through presidential regulation number 2 of 2022 concerning National Entrepreneurship Development to encourage entrepreneurial growth until 2024 the ideal number of 3.95% of the total population of Indonesia can be achieved. This study aims to analyze the entrepreneurial program in the natural school curriculum. The research subject is one of the natural schools in Majalengka Regency. The research uses a qualitative descriptive method with data collection instruments in the form of observation, interviews, and documentation studies. Data analysis uses the Miles and Huberman technique. The results of the study found that entrepreneurial skills were formed in the curriculum through the Friday market program as a means of developing entrepreneurial skills including believing and being optimistic, task and result-oriented, daring to take risks and like challenges, leadership, originality, future-oriented emerged through the Friday market program, the program is intended for all students with class VI in charge. The Friday market program provides a real picture of market life and gets real experience of economic activities that occur in everyday life.